Selective porous gates made from colloidal silica nanoparticles - Nisticò, Roberto (Beilstein J Nanotechnol, 2015)
Highly selective porous films were prepared by spin-coating deposition of colloidal silica nanoparticles on an appropriate macroporous substrate. Silica nanoparticles very homogenous in size were obtained by sol–gel reaction of a metal oxide silica precursor, tetraethyl orthosilicate (TEOS), and using polystyrene-block-poly(ethylene oxide) (PS-b-PEO) copolymers as soft-templating agents. Nanoparticles synthesis was carried out in a mixed solvent system. After spin-coating onto a macroporous silicon nitride support, silica nanoparticles were calcined under controlled conditions. An organized nanoporous layer was obtained characterized by a depth filter-like structure with internal porosity due to interparticle voids. Permeability and size-selectivity were studied by monitoring the diffusion of probe molecules under standard conditions and under the application of an external stimulus (i.e., electric field). Promising results were obtained, suggesting possible applications of these nanoporous films as selective gates for controlled transport of chemical species in solution.